How lucky you are [large type] - Lewis, Kristyn Kusek (Thorndike Press, 2013)
Waverly, Kate, and Amy are a tight-knit trio that's always had Waverly at its center. But now Waverly's cozy bakery is facing financial ruin. Kate's husband is on track to be the next governor, but unsettling questions are brewing in their future. And stay-at-home mom Amy's life is perfect on paper, until a horrific secret threatens to reveal itself. As life's pressures begin to tear the three women apart, Waverly knows she has some big decisions to make.